Rapid characterization of diesel fuel by infrared spectroscopy - Baldrich Ferrer, Carlos A.; Novoa Mantilla, Luz Ángela (CT&F - Ciencia, Tecnología y Futuro, 2006)
It is described an analytical method to characterize a diesel sample in a three minutes period using a portable infrared analyzer. The new models incorporated in the equipment were developed using the software of the equipment and analytical data generated in Instituto Colombiano del Petróleo (ICP), Ecopetrol S.A. labs. Based on this technique it is possible to obtain information about total aromatic content, sulphur content, polynuclear aromatic content and distillation temperatures in a diesel fuel sample. According to the validation results that showed some error bigger than the reproducibility of the original methods, it is recommended to use the proposed method as a semi quantitative one.